Orfeo y Dionisos en el origen de la poesía en María Zambrano y José Lezama Lima - María Carrillo Espinosa (Caravelle)
The aim of comparing María Zambrano’s and Lezama Lima’s essays is to show some ressemblances with regard to Orphism as a poetical origin. Based on a clear rejection of Aristotelian logic, both propose a return to the mythical world through Orpheus and Dionysus. For both of them, poetry is due to Orphic rituals, such as the descent into the underworld, the Dionysian inebriation and the creation of transient images.